WNK2 may promote ovarian cancer progression by upregulating POU5F1B - Fengjie Li; Yongqin Jia; Xiaoli Min; Pangyang Zhang; Yudi Li; Deng Li; Lanqin Cao; Yanzhou Wang; Zhiqing Liang (PLoS ONE, 2026)
Ovarian cancer (OC) remains the most lethal gynecologic malignancy. Our previous work showed that WNK lysine-deficient protein kinase 2 (WNK2) promotes OC cell proliferation and migration. To clarify the molecular basis of WNK2-driven OC progression, here, we performed transcriptome sequencing to identify WNK2-regulated mRNAs and noncoding RNAs. We validated candidate targets using qRT-PCR and Western blot analyses. Functional assays, including CCK-8, colony formation, and Transwell assays, evaluated the role of POU5F1B and its capacity to rescue the effects of WNK2 knockdown. POU5F1B is a promising OC therapeutic target, mediating WNK2-driven oncogenesis in xenograft models (n = 10). Because AKT acts downstream of POU5F1B, we examined AKT phosphorylation and found that POU5F1B displayed clear oncogenic activity in OC cells. WNK2 upregulated POU5F1B mRNA and protein levels, while POU5F1B overexpression reversed the tumor-suppressive effects caused by WNK2 depletion. Mechanistically, WNK2 silencing decreased AKT phosphorylation, which POU5F1B overexpression restored. Together, these results demonstrate that WNK2 promotes OC progression by upregulating the validated oncogene POU5F1B and activating AKT signaling. These findings establish WNK2 as an oncogenic driver and a promising therapeutic target in OC.